Media Visual Mempengaruhi Pengetahuan Siswi Tentang Menstruasi - Eka Fitri Amir; Andi Wilda Arianggara; Huzaima (YAYASAN PENDIDIKAN MANDIRA CENDIKIA, 2022)
Menstruation by adolescents will be a traumatic event when they do not know the information about menstruation in advance. With an event like this, what is needed by adolescents is information about the nature of menstruation and its relationship with processes and changes during menstruation, so that it can affect the attitude of adolescents in dealing with menstrual events. In today's global world, information is something that is needed for human life so that many people from the intellect develop media so that information can be easily obtained and understood by the recipient of information. This study aims to determine the influence of the use of visual and audio-visual media on knowledge about menstruation in Student at the Maskanul Hufadz Islamic Boarding School, Batam City, samples selected as many as 20 Student with sampling techniques proportionate stratified random sampling. Data collection tools use questionnaires. The results of the study before being given counseling using visual media , most of the students' knowledge is in the sufficient category and after being given counseling, the knowledge of female students is mostly in the category either with p-value = 0.022 or in other words There is an influence between providing counseling using visual media on students' knowledge about menstruation . Keywords: Visual Media, Knowledge, Menstruation